Réponses

Meilleure réponse !
2014-05-04T11:57:37+02:00
Bonjour

N°V

A = (7-3x)(9x-3) = 63x -21 - 27x² + 9x = -27x² +72x -21

B = (5x+2)² = 25x² + 20x  +4

C = (4a +6)(-3 -5a) = - 12a - 20a² - 18 - 30a = -20a² - 42a -18

D = (4 -x)² = 16 - 8x + x²

N°VI

A = (x+3) +(4x -5) = x +3 +4x -5 = 5x -2

B = 6 -2t - (4t -8) = 6 -2t -4t +8 = -6t +14

C = - (8a+3) - 4a = -8a -3 -4a = - 12a -3

D = (3y +7)+ (-5y +3) = 3y +7 -5y +3 = -2y +10

E = 5z -6 - (7 -2z) +3z = 5z -6 -7 +2z +3z = 10z - 13

F = (3 -4x) - (-2x +8) = 3-4x +2x -8 = -2x -5

N°VII

3(2x-7) -5x = 6x - 21 -5x = x -21
pour x = 4 on a : 4-21 = -17
pour x = 0, on a : -21
pour x = -2, on a : -2-21 = -23

(x-4)(x-2) = x² -2x -4x +8 = x² -6x +8
pour x = 4 ,  = 16 -24 +8 = 0
pour x = 0 , = 8
pour x = -2, = 4+12+8 = 24

(2 -x)² = 4 - 4x +x²
pour x = 4, = 4-16+16 = 4
pour x = 0, = 4
pour x = -2 : 4 +8 + 4 = 16